Cardiac phenotype of mitochondrial creatine kinase knockout mice is modified on a pure C57BL/6 genetic background. - Lygate, C; Hunyor, I; Medway, D; de Bono, J; Dawson, D; Wallis, J; Sebag-Montefiore, L; Neubauer, S (2009)
UNLABELLED: Discrepant results for the phenotype of mitochondrial creatine kinase knockout mice (Mt-CK(-/-)) could be due to mixed genetic background and use of non-littermate controls. We therefore backcrossed with C57BL/6J for >8 generations, followed by extensive in vivo cardiac phenotyping. Echocardiography and in vivo LV haemodynamics were performed in independent cohorts at 20-40 weeks and 1 year. No significant differences were observed for ECG, LV volumes, pressures, and systolic or diastolic function compared to littermate controls. Furthermore, responses to dobutamine were not different, indicating preserved contractile reserve. Contrary to published reports using Mt-CK(-/-) on a mixed background, we observed normal LV weights even in year old mice, and gene expression of common hypertrophic markers were not elevated. However, previously undetected adaptations were observed: an increase in activity of the cytosolic MM-CK isoenzyme (+20% vs WT, P=0.0009), and of citrate synthase (+18% vs WT, P=0.0007), a marker for mitochondrial volume. In a 3-week voluntary wheel running protocol, Mt-CK(-/-) ran significantly less per day (P=0.009) and attained lower maximum speed compared to controls (P=0.0003), suggesting impaired skeletal muscle function. MM-CK isoenzyme activity was significantly elevated in soleus but not gastrocnemius muscle of KO mice, and citrate synthase activities were normal in both, suggesting compensatory mechanisms are incomplete in skeletal muscle. CONCLUSIONS: in contrast to previous reports using a mixed genetic background, Mt-CK(-/-) on a C57BL/6 background do not develop LV hypertrophy or dysfunction even up to 1 year, and this may be explained by a compensatory increase in MM-CK activity and mitochondrial volume.